A rare earth-poor dual-phase composite magnetic material and preparation method thereof
By reducing the content of rare earth elements and controlling the content of other elements in the biphase composite magnetic material, combined with multi-field coupling heat treatment and magnetic coating technology, the high cost and poor magnetic performance of high residual magnets are solved. The problem is that high residual magnetism, low coercivity and low cost effects are achieved.
Patent Information
- Application Number
- CN202411372610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing high residual magnetism and low coercive force biphasic composite magnets have high cost, low residual magnetism and high coercive force due to high content of rare earth elements, and the magnetic performance degradation caused by magnetic adhesives under the limitations of the preparation technology.
Using the general structural formula of rare earth-limited biphasic composite magnetic material (REaNd1-a)b(Fe1-cCoc)100-b-e-f-g-h(B1-dQd)eCufTgMh, through induction + arc smelting, single-roll quenching, multi-field coupling heat treatment and magnetism The coating preparation method is to control the content of light rare earths, main groups, low melting point and grain refinement elements, reduce the substitute mole fraction of rare earth elements, and improve the amorphous formation ability and magnetic exchange coupling effect.
Magnetic materials with high residual magnetism, low coercivity and low cost are realized, which improves the temperature stability, oxidation resistance and grain refinement of the material, and meets the high residual magnetism and low coercivity requirements of electromagnetic conversion devices.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetic materials, and in particular to a rare earth-poor dual-phase composite magnetic material and a preparation method thereof. Background Art
[0002] Dual-phase composite magnetic materials are a new type of magnetic material formed by the uniform dispersion of soft magnetic phase and hard magnetic phase at the nanoscale, through the exchange coupling of adjacent atomic magnetic moments. With the continuous development of new component systems and the deepening of theoretical research, the research on dual-phase composite magnetic materials is mainly focused on two directions. The first is to break through the maximum magnetic energy limit of rare earth permanent magnet materials, develop dual-phase composite magnets with high remanence and high coercivity, promote their application in generators, sensors and other fields, and accelerate the development of electronic devices towards miniaturization and high efficiency; the second is to carry out the research and development of high remanence and low coercivity dual-phase composite magnetic materials, improve the material's charging and demagnetization (soft and hard magnetic function conversion) characteristics, promote its application in electromagnetic conversion devices such as magnetic switches, reactors, transformers, and promote the development of devices towards high electromagnetic conversion efficiency and low loss.
[0003] At present, for high remanence and high coercivity dual-phase composite magnets, the maximum magnetic energy product of bulk materials has reached 55.5MGOe, which is very close to that of single-phase sintered NdFeB magnets, while the maximum magnetic energy product of nano-multilayer film structure materials has reached 61.1MGOe, breaking through the maximum magnetic energy limit of rare earth permanent magnet materials. However, for high remanence and low coercivity dual-phase composite magnets, there are still two problems: First, due to the limitation of the material composition system, the rare earth element content is generally high, although it is easy to form RE2Fe 14 The B hard magnetic phase and the rare earth-rich phase that acts as a grain boundary lubricant ensure the exchange coupling between the soft and hard magnetic phases while preventing the magnet from cracking. However, the high rare earth content also causes the over-utilization of key rare earth resources and the increase of the hard magnetic phase content, resulting in low remanence, large coercive force and high cost of the two-phase composite magnetic material. On the other hand, due to the limitations of preparation technology, after the strips are bonded into magnets, the magnetic properties of the magnets are significantly reduced compared to the two-phase composite magnetic strips due to the doping of non-magnetic binders. Summary of the invention
[0004] In view of the problems of poor magnetic properties and high cost of the above-mentioned existing high remanence and low coercivity dual-phase composite magnetic materials, the present invention provides a rare earth-poor dual-phase composite magnetic material and a preparation method thereof. The rare earth-poor dual-phase composite magnetic material of the present invention has the advantages of high remanence, low coercivity, and low cost, and is conducive to application in electromagnetic conversion devices such as magnetically controlled switches, inductors, and transformers.
[0005] The present invention is achieved through the following technical solutions:
[0006] A rare earth-poor two-phase composite magnetic material, the general structural formula of the rare earth-poor two-phase composite magnetic material is: (RE a Nd 1-a ) b (Fe 1-c Co c ) 100-b-e-f-g-h (B 1-d Q d ) e Cu f T g M h ;
[0007] Among them, RE is a light rare earth element, Q is a main group element, T is a low melting point element, and M is a grain refining element;
[0008] a , c , d Respectively represent the molar fractions of RE, Co, and Q replacing Nd, Fe, and B elements, satisfying 0≤ a ≤0.2,0≤ c ≤0.05,0≤ d ≤1;
[0009] b、e、f、g、h Respectively represent the molar fractions of the total content of Nd and light rare earth elements, the total content of B and main group elements, Cu elements, low melting point elements, and grain refining elements, satisfying 4≤ b ≤7, 6≤ e ≤10,0≤ f ≤1,0≤ g ≤1,0≤ h ≤2.
[0010] Furthermore, the light rare earth element RE is one or two of La, Ce and Y;
[0011] And / or, the main group element Q is one or two of C, N, Si and P;
[0012] And / or, the low melting point element T is one or two of Ga, Ge and Al;
[0013] And / or, the grain refining element M is one or two of Ti, Nb, Mo and Ta.
[0014] A method for preparing a rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0015] Weighing raw materials according to the general structural formula of the rare earth-poor dual-phase composite magnetic material, smelting the raw materials several times under a protective atmosphere to obtain a uniformly smelted alloy ingot;
[0016] After the alloy ingot is crushed, it is heated to a molten state under a protective atmosphere, and the resulting melt is overflowed onto a cooling roller to form an amorphous thin strip;
[0017] The amorphous thin ribbon is subjected to a magnetic-thermal-mechanical multi-field coupled heat treatment to obtain a dual-phase composite magnetic material nanocrystalline ribbon;
[0018] The nanocrystalline strips of the dual-phase composite magnetic material are powdered and sieved to obtain a precursor magnetic powder, the precursor magnetic powder is mixed with a coupling agent, a curing agent, a binder and a filler for pressing, and the pressed magnet is subjected to a heating reaction to obtain a bonded magnet;
[0019] An alpha-Fe magnetic coating is uniformly coated on the surface of the bonded magnet to obtain a rare earth-poor dual-phase composite magnetic material.
[0020] Furthermore, the raw materials are melted several times under a protective atmosphere, specifically: in an argon atmosphere, Nd, light rare earth elements RE, B, and low melting point elements T are placed at the bottom, Fe, Co, Cu, main group elements Q, and grain refining elements M are placed at the top, and while the bottom raw materials are melted by an induction coil, a 60-120A current arc is used to melt the top raw materials, and the melting is performed 4-6 times.
[0021] Furthermore, the thickness of the amorphous thin strip is 15-30 μm, the width is 5-10 mm, and the rotation speed of the cooling roller is 25-60 m / s.
[0022] Furthermore, the magnetic-thermal-mechanical multi-field coupling heat treatment is specifically as follows: heating the temperature to 500-650°C at a heating rate of 2-5°C / min, applying an external magnetic field of 1-2T and a pressure of 100-300MPa during the heating process, and keeping the temperature for 5-15min.
[0023] Furthermore, the screening is specifically through a 120-mesh sieve, the pressing pressure is 1500-2000 MPa, and the pressing time is 30-60 s.
[0024] Furthermore, the coupling agent is KH-550 silane, the curing agent is diaminodiphenyl sulfone, the adhesive is epoxy resin, and the filler is acetone;
[0025] In the mixture of the precursor magnetic powder, coupling agent, curing agent, adhesive and filler, the coupling agent accounts for 1-2wt.%, the curing agent accounts for 20-25wt.%, the adhesive accounts for 3-5wt.%, and the filler accounts for 10-15wt.%.
[0026] Furthermore, the heating reaction is specifically: keeping the temperature at 160-180° C. for 1-2 hours under the protection of argon atmosphere, and then cooling to room temperature.
[0027] Further, the thickness of the α-Fe magnetic coating does not exceed 0.5 mm;
[0028] And / or, the α-Fe magnetic coating is composed of 30-35wt.% of α-Fe magnetic powder, 5-10wt.% of epoxy resin, 3-5wt.% of nano-silicon dioxide and 50-62wt.% of acetone;
[0029] And / or, the particle size of the α-Fe magnetic powder is 10-125 μm.
[0030] Compared with the prior art, the present invention has the following beneficial technical effects:
[0031] The present invention is a rare earth-poor dual-phase composite magnetic material, and the light rare earth element content used is much lower than the high rare earth content required by conventional dual-phase composite magnetic materials. The rare earth-poor content of the present invention can not only suppress the excessive high coercivity RE2Fe 14 The formation of B hard magnetic phase increases the content of high saturation magnetization intensity α-Fe, which is beneficial to increase the remanence and reduce the coercive force. In addition, the two-phase composite magnetic material has the advantages of high temperature stability, excellent heat resistance and oxidation resistance due to its low rare earth content, which is more conducive to the practical application of the material.
[0032] In addition, in the rare earth-poor dual-phase composite magnetic material of the present invention, by controlling the content of B element, not only can the amorphous forming ability of the material be improved, the crystallization temperature difference between the soft and hard magnetic phases be shortened, the premature precipitation of the soft magnetic phase leading to grain coarsening can be prevented, and the formation of a fine and uniform microstructure of grains can be promoted, but also the formation of Fe3B soft magnetic phase with low saturation magnetization intensity and paramagnetic Nd can be avoided. 1.1 Fe4B4 and other B-rich phases lead to reduced remanence. The addition of a small amount of Co increases the magnetic exchange interaction with Fe, which is beneficial to improving the high-temperature stability and remanence of the material. The addition of a small amount of the main group element Q not only reduces the anisotropy field of the magnetic phase, achieving the purpose of reducing the coercive force, but also inhibits the formation of impurity phases other than soft and hard magnetic phases (such as grain refinement elements and B elements that easily form a 1:2 impurity phase), increases the content of the magnetic phase, and thus increases the remanence. By controlling the content of the low-melting-point element T, on the one hand, the low-melting-point element can replace the rare earth-rich phase in conventional magnets, and exist in the form of precipitation at the grain boundaries of the soft and hard magnetic phases, playing a lubricating role, which is beneficial to the rotation of the soft and hard magnetic phase grains and preventing the material from cracking. The grain refinement element M promotes grain refinement by segregating at the grain boundaries, which is beneficial to improving the exchange coupling between the soft and hard magnetic phases, achieving the effect of improving the remanence of the material.
[0033] Furthermore, the rare earth element RE of the present invention is one or two of La, Ce and Y. The high-abundance rare earth elements La, Ce and Y are selected to partially replace the precious metal Nd, which is not only conducive to saving key rare earth resources and saving costs, but also generates an anisotropy field much smaller than that of Nd2Fe14 B's RE2Fe 14 B hard magnetic phase, thereby reducing the coercive force.
[0034] In the preparation method of the rare earth-poor dual-phase composite magnetic material described in the present invention, a multi-field coupling heat treatment method is used to crystallize the amorphous thin strip of the dual-phase composite magnetic material. The magnetic-thermal-mechanical multi-field coupling effect can not only reduce the crystallization temperature of the soft and hard magnetic phases, shorten the crystallization time, and promote the crystallization of the amorphous thin strip, but also significantly refine the grain size by changing the crystallization dynamics of the magnetic phase grains, improve the exchange coupling effect of the soft and hard magnetic phases, and thus improve the remanence of the material. At the same time, a magnetic coating step is added on the basis of the original bonded magnet molding. By coating a layer of α-Fe magnetic coating with high saturation magnetization intensity on the surface of the bonded magnet, not only can the bonding force between the magnetic powders in the bonded magnet be increased, the overall strength of the magnet can be improved, but also the remanence of the material can be further increased and the coercive force can be reduced, thereby meeting the magnetic performance requirements of high remanence and low coercive force dual-phase composite magnetic materials for electromagnetic conversion devices such as magnetic switches, reactors, and transformers. DETAILED DESCRIPTION
[0035] The present invention is described in detail below:
[0036] The present invention provides a rare earth-poor dual-phase composite magnetic material, the general formula of which is: (RE a Nd 1-a ) b (Fe 1- c Co c ) 100-b-e-f-g-h (B 1-d Q d ) e Cu f T g M h ; Among them, RE is a light rare earth element, Q is a main group element, T is a low melting point element, and M is a grain refining element; a , c , d Respectively represent the molar fractions of RE, Co, and Q replacing Nd, Fe, and B elements, satisfying 0≤ a ≤0.2,0≤ c ≤0.05,0≤ d ≤1; b、e、f、g、h Respectively represent the molar fractions of the total content of Nd and light rare earth elements, the total content of B and main group elements, Cu elements, low melting point elements, and grain refining elements, satisfying 4≤ b ≤7, 6≤ e ≤10,0≤ f ≤1,0≤ g ≤1,0≤ h ≤2.
[0037] The light rare earth element RE is one or two of La, Ce and Y.
[0038] The main group element Q is one or two of C, N, Si and P.
[0039] The low melting point element T is one or two of Ga, Ge and Al.
[0040] The grain refining element M is one or two of Ti, Nb, Mo and Ta.
[0041] The present invention also provides a method for preparing the above-mentioned rare earth-poor dual-phase composite magnetic material, comprising five steps: ① induction + arc melting, ② single-roller spinning, ③ multi-field coupling heat treatment, ④ bonding molding, and ⑤ magnetic coating.
[0042] ① The specific process of induction + arc melting is: weigh and proportion Nd, light rare earth elements RE, Fe, Co, B, Cu, main group elements Q, low melting point elements T, and grain refining elements M according to the atomic percentages described in the general formula above, put the weighed raw materials into the crucible of the vacuum melting furnace, put Nd, rare earth elements RE, B, and low melting point elements T at the bottom of the crucible, and put Fe, Co, Cu, main group elements Q and grain refining elements M at the top. While heating and melting the bottom raw materials with an induction coil under the protection of an argon atmosphere, a 60~120A high current arc is used at the top for local high temperature melting. In this way, the induction and arc melting are combined for 4~6 times to obtain a uniformly melted alloy ingot. The melting points of the elements in the dual-phase composite material are quite different. The combination of induction melting and arc melting can promote the full melting and bonding of raw materials with different melting points, so that the elements in the alloy ingot are evenly distributed.
[0043] ② The specific process of single-roll quenching is: the alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy pieces in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a high-speed rotating cooling copper roller to form an amorphous ribbon with a thickness of 15-30 μm and a width of 5-10 mm. In order to ensure that the amorphous state of the amorphous ribbon is good, the rotation rate of the cooling copper roller is 25-60 m / s.
[0044] ③ The specific process of multi-field coupling heat treatment is as follows: the amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 500~650℃ at a heating rate of 2~5℃ / min. During the heating process, an external magnetic field of 1~2T and a pressure of 100~300MPa are applied simultaneously, and the temperature is kept for 5~15min. The low heating rate of 2~5℃ / min can ensure that the amorphous ribbon is heated uniformly, and avoid abnormal precipitation and growth of soft and hard magnetic phase grains due to uneven heating. The temperature range of 500~650℃ and the holding time of 5~15min can not only promote the smooth precipitation of soft and hard magnetic phase nano-grains in the amorphous phase, but also shorten the growth time of nano-grains, promote grain refinement, enhance the nano-exchange coupling effect between grains, and help improve the remanence. The coupling effect of external magnetic field and pressure can not only reduce the crystallization temperature of soft and hard magnetic phases, shorten the crystallization time, and promote the crystallization of amorphous thin ribbons, but also significantly refine the grain size by changing the crystallization kinetics of magnetic phase grains, improve the exchange coupling effect of soft and hard magnetic phases, and thus improve the remanence of the material. After the heat preservation is completed, the thin ribbon is quickly cooled to room temperature to prevent the nano-grains in the amorphous thin ribbon from growing slowly during the cooling process, and a nano-crystalline strip of a dual-phase composite magnetic material is obtained.
[0045] ④ The specific process of bonding molding is as follows: the dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained, which is beneficial to increase the density of the bonded magnet and thus improve the magnetic properties. The precursor magnetic powder is mixed with a coupling agent (1~2wt.% KH-550 silane), a curing agent (20~25wt.% diaminodiphenyl sulfone (DDS)), a binder (3~5wt.% epoxy resin), and a filler (10~15wt.% acetone) and injected into a mold, and then placed in a hydraulic press for pressing, with the pressure set to 1500~2000MPa and the pressing time being 30~60s. Under the action of this pressure and pressure time, the density of the magnet can be significantly increased, which is beneficial to improving the magnetic properties and mechanical strength of the magnet. The pressed magnet is placed in a tubular furnace, kept at 160~180℃ for 1~2h under the protection of an argon atmosphere, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0046] ⑤ The specific process of magnetic coating is: a layer of α-Fe magnetic coating is uniformly coated on the surface of the bonded magnet obtained in step ④, and the thickness of the α-Fe magnetic coating does not exceed 0.5mm. The α-Fe magnetic coating is composed of 30~35wt.% α-Fe magnetic powder (particle size is 10~125μm), 5~10wt.% epoxy resin, 3~5wt.% nano-silicon dioxide, and 50~62wt.% acetone. α-Fe itself has a very high saturation magnetization intensity. Coating it on the surface of the bonded magnet can increase the remanence of the magnet and reduce the coercive force, which is conducive to obtaining a dual-phase composite magnet with higher remanence and low coercive force.
[0047] The embodiments of the present invention will be described in detail below in conjunction with the examples. The implementation cases are preferred embodiments of the present invention and should not be used to limit the scope of the present invention. In the following examples, the methods and experimental equipment used are all conventional methods and instruments unless otherwise specified.
[0048] Example 1
[0049] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (La 0.1 Y 0.1 Nd 0.8 )4Fe 90 B6.
[0050] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0051] ① Induction + arc melting: La, Y, Nd, Fe, and B elements are weighed and proportioned according to the atomic percentage described in the above general formula, and the weighed raw materials are placed in the crucible of a vacuum melting furnace. La, Y, Nd, and B elements are placed at the bottom of the crucible, and Fe element is placed at the top. While the bottom raw materials are heated by an induction coil under the protection of an argon atmosphere, a 60A arc is used on the top for local high-temperature melting. This induction and arc combination melting is repeated 6 times to obtain a uniformly smelted alloy ingot.
[0052] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 25 m / s to form an amorphous thin strip with a thickness of 30 μm and a width of 5 mm.
[0053] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 500°C at a heating rate of 2°C / min. During the heating process, an external magnetic field of 1T and a pressure of 100MPa are applied simultaneously, and the temperature is kept for 15 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0054] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strips obtained in step ③ are mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (61wt.%) is mixed with a coupling agent (1wt.% KH-550 silane), a curing agent (20wt.% diaminodiphenyl sulfone (DDS)), a binder (3wt.% epoxy resin), and a filler (15wt.% acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 1500MPa and the pressing time is 60s. The pressed magnet is placed in a tubular furnace, kept at 160°C for 2h under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0055] ⑤ Magnetic coating: A magnetic coating composed of 35wt.% of 10-125μm particle size α-Fe magnetic powder, 10wt.% of epoxy resin, 5wt.% of nano-silicon dioxide, and 50wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.5mm to obtain the final rare earth-poor two-phase composite magnet.
[0056] Example 2
[0057] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (Ce 0.2 Nd 0.8 )4Fe 90 B6.
[0058] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0059] ① Induction + arc melting: Weigh and proportion the Ce, Nd, Fe, and B elements according to the atomic percentage described in the above general formula, put the weighed raw materials into the crucible of the vacuum melting furnace, put the Ce, Nd, and B elements at the bottom of the crucible, and the Fe element at the top. While the bottom raw materials are heated by an induction coil under the protection of an argon atmosphere, a 60A arc is used on the top for local high-temperature melting. This induction and arc melting are combined for 4 times to obtain a uniformly smelted alloy ingot.
[0060] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 60 m / s to form an amorphous thin strip with a thickness of 15 μm and a width of 10 mm.
[0061] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 650°C at a heating rate of 5°C / min. During the heating process, an external magnetic field of 1T and a pressure of 100MPa are applied simultaneously, and the temperature is kept for 5 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0062] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (58 wt.%) is mixed with a coupling agent (2 wt.% of KH-550 silane), a curing agent (25 wt.% of diaminodiphenyl sulfone (DDS)), a binder (5 wt.% of epoxy resin), and a filler (10 wt.% of acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 2000 MPa and the pressing time is 30 s. The pressed magnet is placed in a tubular furnace, kept at 180°C for 1 hour under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0063] ⑤ Magnetic coating: A magnetic coating composed of 30wt.% of 10-125μm particle size α-Fe magnetic powder, 5wt.% of epoxy resin, 3wt.% of nano-silicon dioxide, and 62wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.5mm to obtain the final rare earth-poor two-phase composite magnet.
[0064] Example 3
[0065] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula Nd7(Fe 0.95 Co 0.05 ) 83 B 10 .
[0066] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0067] ① Induction + arc melting: Weigh and proportion the Nd, Fe, Co, and B elements according to the atomic percentage described in the above general formula, put the weighed raw materials into the crucible of the vacuum melting furnace, put the Nd and B elements at the bottom of the crucible, and put the Fe and Co elements on the top. While the bottom raw materials are heated by an induction coil under the protection of argon atmosphere, a 100A arc is used at the top for local high-temperature melting. This induction and arc combination melting is repeated 5 times to obtain a uniformly smelted alloy ingot.
[0068] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 50 m / s to form an amorphous thin strip with a thickness of 18 μm and a width of 8 mm.
[0069] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 600°C at a heating rate of 4°C / min. During the heating process, an external magnetic field of 1.5T and a pressure of 200MPa are applied simultaneously, and the temperature is kept for 10 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0070] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (60.5wt.%) is mixed with a coupling agent (1.5wt.% KH-550 silane), a curing agent (22wt.% diaminodiphenyl sulfone (DDS)), a binder (4wt.% epoxy resin), and a filler (12wt.% acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 1800MPa and the pressing time is 45s. The pressed magnet is placed in a tubular furnace, kept at 150°C for 1.5h under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0071] ⑤ Magnetic coating: A magnetic coating composed of 32wt.% of 10-125μm particle size α-Fe magnetic powder, 8wt.% of epoxy resin, 4wt.% of nano-silicon dioxide and 56wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.3mm to obtain the final rare earth-poor two-phase composite magnet.
[0072] Example 4
[0073] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (Ce 0.2 Nd 0.8 )4(Fe 0.95 Co 0.05 ) 86 (B 0.99 C 0.1 )7Cu1Ga1Nb1.
[0074] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0075] ① Induction + arc melting: Weigh and proportion the elements Ce, Nd, Fe, Co, B, C, Cu, Ga, and Nb according to the atomic percentages described in the above general formula, put the weighed raw materials into the crucible of a vacuum melting furnace, put Ce, Nd, B, and Ga elements at the bottom of the crucible, and put Fe, Co, C, Cu, and Nb elements on the top. While the bottom raw materials are heated by an induction coil under the protection of an argon atmosphere, a 120A arc is used on the top for local high-temperature melting. This induction and arc melting are combined for 4 times to obtain a uniformly smelted alloy ingot.
[0076] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 50 m / s to form an amorphous thin strip with a thickness of 18 μm and a width of 8 mm.
[0077] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 650°C at a heating rate of 5°C / min. During the heating process, an external magnetic field of 2T and a pressure of 300MPa are added simultaneously, and the temperature is kept for 5 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0078] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (58 wt.%) is mixed with a coupling agent (2 wt.% of KH-550 silane), a curing agent (20 wt.% of diaminodiphenyl sulfone (DDS)), a binder (5 wt.% of epoxy resin), and a filler (15 wt.% of acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 1800 MPa and the pressing time is 45 s. The pressed magnet is placed in a tubular furnace, kept at 160°C for 2 hours under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0079] ⑤ Magnetic coating: A magnetic coating composed of 35wt.% of 10-125μm particle size α-Fe magnetic powder, 10wt.% of epoxy resin, 5wt.% of nano-silicon dioxide, and 50wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.5mm to obtain the final rare earth-poor two-phase composite magnet.
[0080] Example 5
[0081] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (Ce 0.2 Nd0.8 )4(Fe 0.95 Co 0.05 ) 86 (B 0.99 N 0.005 P 0.005 )6Cu1Ge 0.5 Al 0.5 Ti1Mo1.
[0082] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0083] ① Induction + arc melting: Weigh and proportion Ce, Nd, Fe, Co, B, N, P, Cu, Ge, Al, Ti, and Mo elements according to the atomic percentage described in the above general formula, put the weighed raw materials into the crucible of the vacuum melting furnace, put Ce, Nd, B, Ge, and Al elements at the bottom of the crucible, and put Fe, Co, N, P, Cu, Ti, and Mo elements on the top. While the bottom raw materials are heated by an induction coil under the protection of argon atmosphere, a 120A arc is used on the top for local high-temperature melting. This induction and arc melting are combined for 4 times to obtain a uniformly smelted alloy ingot.
[0084] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 50 m / s to form an amorphous thin strip with a thickness of 18 μm and a width of 8 mm.
[0085] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 650°C at a heating rate of 5°C / min. During the heating process, an external magnetic field of 2T and a pressure of 300MPa are applied simultaneously, and the temperature is kept for 5 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0086] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (58 wt.%) is mixed with a coupling agent (2 wt.% of KH-550 silane), a curing agent (20 wt.% of diaminodiphenyl sulfone (DDS)), a binder (5 wt.% of epoxy resin), and a filler (15 wt.% of acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 1800 MPa and the pressing time is 45 s. The pressed magnet is placed in a tubular furnace, kept at 160°C for 2 hours under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0087] ⑤ Magnetic coating: A magnetic coating composed of 35wt.% of 10-125μm particle size α-Fe magnetic powder, 10wt.% of epoxy resin, 5wt.% of nano-silicon dioxide, and 50wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.5mm to obtain the final rare earth-poor two-phase composite magnet.
[0088] Example 6
[0089] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (Ce 0.2 Nd 0.8 )4(Fe 0.95 Co 0.05 ) 86 (B 0.99 C 0.005 Si 0.005 )6Cu1Ga1Ta2.
[0090] The method for preparing the above rare earth-poor dual-phase composite magnetic material comprises the following steps:
[0091] ① Induction + arc melting: Weigh and proportion the elements Ce, Nd, Fe, Co, B, C, Si, Cu, Ga, and Ta according to the atomic percentages described in the general formula above, put the weighed raw materials into the crucible of a vacuum melting furnace, put Ce, Nd, B, and Ga elements at the bottom of the crucible, and put Fe, Co, C, Si, Cu, and Ta elements at the top. While the bottom raw materials are heated by an induction coil under the protection of an argon atmosphere, a 120A arc is used on the top for local high-temperature melting. This induction and arc melting are combined for 4 times to obtain a uniformly smelted alloy ingot.
[0092] ② Single-roll quenching: The alloy ingot obtained in step ① is broken into small pieces and placed in a quartz tube in a single-roll quenching furnace. After the single-roll quenching furnace is evacuated and high-purity argon is introduced, the alloy fragments in the quartz tube are reheated to a molten state, and then the melt is overflowed onto a cooling copper roller with a rotation rate of 50 m / s to form an amorphous thin strip with a thickness of 18 μm and a width of 8 mm.
[0093] ③Multi-field coupling heat treatment: The amorphous ribbon formed in step ② is placed in a magnetic-thermal-mechanical multi-field coupling heat treatment furnace, and the furnace temperature is raised to 650°C at a heating rate of 5°C / min. During the heating process, an external magnetic field of 2T and a pressure of 300MPa are applied simultaneously, and the temperature is kept for 5 minutes. After the insulation is completed, the amorphous ribbon is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline ribbon.
[0094] ④ Bonding molding: The dual-phase composite magnetic material nanocrystalline strip obtained in step ③ is mechanically ground into powder, passed through a 120-mesh sieve, and a precursor magnetic powder with uniform particle size is obtained. The precursor magnetic powder (58 wt.%) is mixed with a coupling agent (2 wt.% of KH-550 silane), a curing agent (20 wt.% of diaminodiphenyl sulfone (DDS)), a binder (5 wt.% of epoxy resin), and a filler (15 wt.% of acetone) and injected into a mold, and then placed in a hydraulic press for pressing. The pressure is set to 1800 MPa and the pressing time is 45 s. The pressed magnet is placed in a tubular furnace, kept at 160°C for 2 hours under argon atmosphere protection, and then cooled to room temperature with the furnace to obtain a bonded magnet.
[0095] ⑤ Magnetic coating: A magnetic coating composed of 35wt.% of 10-125μm particle size α-Fe magnetic powder, 10wt.% of epoxy resin, 5wt.% of nano-silicon dioxide, and 50wt.% of acetone is uniformly coated on the surface of the bonded magnet obtained in step ④, and the coating thickness is 0.5mm to obtain the final rare earth-poor two-phase composite magnet.
[0096] Comparative Example 1
[0097] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula Nd4Fe 90 B6. The preparation method is as described in Specific Example 1.
[0098] Comparative Example 2
[0099] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula Nd7Fe 83 B 10 The preparation method is as in Specific Example 3.
[0100] Comparative Example 3
[0101] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (La 0.1 Y 0.1 Nd 0.8 )4Fe 90 B6. The preparation method refers to Specific Example 1. The difference is that in step ③, conventional heat treatment is used instead of multi-field coupling heat treatment, that is: the amorphous thin strip formed in step ② is placed in a vacuum heat treatment furnace, the furnace temperature is raised to 500°C at a heating rate of 2°C / min, and the temperature is kept for 15 minutes. After the insulation is completed, the amorphous thin strip is quickly air-cooled to room temperature to obtain a dual-phase composite magnetic material nanocrystalline strip.
[0102] Comparative Example 4
[0103] A rare earth-poor dual-phase composite magnetic material, the composition and content of which are expressed by the chemical formula (La0.1 Y 0.1 Nd 0.8 )4Fe 90 B6. The preparation method is similar to that of Specific Example 1. The difference is that the preparation process does not include step ⑤ magnetic coating.
[0104] The residual magnetic induction intensity of the rare earth-poor dual-phase composite magnetic materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was measured by a vibrating sample magnetometer (VSM). B r and coercivity H c , the test results are shown in Table 1.
[0105] Table 1 Magnetic properties test results of rare earth-poor dual-phase composite magnetic materials
[0106]
[0107] As shown in Table 1, compared with the comparative example, the embodiment with element composition adjustment and preparation process optimization has both high remanence and low coercivity characteristics, with remanence reaching above 0.45T and coercivity as low as below 500Oe. By comparing Examples 1 and 2 with Comparative Example 1, it is shown that the use of light rare earth elements La, Y, and Ce to replace part of the Nd element is beneficial to reduce RE2Fe 14The anisotropy field of the B hard magnetic phase reduces the coercivity from 427Oe to below 410Oe, while the remanence is maintained at about 0.45T. The magnetic property test results of Example 3 and Comparative Example 2 show that the addition of a small amount of Co element significantly increases the remanence while keeping the coercivity basically unchanged, indicating that the addition of a small amount of Co element increases the magnetic exchange interaction with the Fe element, and increases the remanence of the material from 0.41T to 0.50T. Examples 4, 5, and 6 are new component systems formed by further adding the excited nucleation element Cu, one or more of the main group elements C, N, Si, and P, one or more of the low melting point elements Ga, Ge, and Al, and one or more of the grain refining elements Ti, Nb, Mo, and Ta on the basis of the elemental components of Examples 2 and 3. By comparing the magnetic properties, it can be seen that after the composite addition of ferromagnetic element Co, excited nucleation element Cu, main group element Q, low melting point element T and grain refinement element M, the remanence of the material is increased from 0.47T to more than 0.53T, and the coercivity is reduced from 410Oe to less than 300Oe, indicating that the composition design method provided by the present invention is conducive to improving the remanence of the two-phase composite magnetic material and reducing the coercivity. By comparing the magnetic properties of the magnets of Example 1 and Comparative Example 3, it can be seen that after the two-phase composite magnetic material is crystallized by multi-field coupling heat treatment, the remanence of the material is increased by 0.03T compared with the conventional heat treatment method, and the coercivity is reduced by 75Oe, indicating that multi-field coupling heat treatment is conducive to obtaining a two-phase composite bonded magnet with high remanence and low coercivity. By comparing Example 1 and Comparative Example 4, it can be seen that after the bonded magnet is surface treated by magnetic coating, the remanence of the magnet is significantly increased from 0.40T to 0.47T, and the coercive force is reduced from 530Oe to 408Oe, indicating that α-Fe magnetic coating has a significant promoting effect on increasing the remanence of the material and reducing the coercive force, which is conducive to obtaining a dual-phase composite bonded magnet with high remanence and low coercive force.
[0108] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a rare earth-poor dual-phase composite magnetic material, characterized in that: The following steps are involved: Weighing raw materials according to the general structural formula of the rare earth-poor dual-phase composite magnetic material, smelting the raw materials several times under a protective atmosphere to obtain a uniformly smelted alloy ingot; The general structural formula of the rare earth-poor dual-phase composite magnetic material is: a Nd 1-a ) b (Fe 1-c Co c ) 100-b-e-f-g-h (B 1-d Q d ) e Cu f T g M h ; Among them, RE is a light rare earth element, Q is a main group element, T is a low melting point element, and M is a grain refining element; a , c , d Respectively represent the molar fractions of RE, Co, and Q replacing Nd, Fe, and B elements, satisfying 0≤ a ≤0.2,0≤ c ≤0.05,0≤ d ≤1; b, e, f, g, h Respectively represent the molar fractions of the total content of Nd and light rare earth elements, the total content of B and main group elements, Cu elements, low melting point elements, and grain refining elements, satisfying 4≤ b ≤7, 6≤ e ≤10,0≤ f ≤1,0≤ g ≤1,0≤ h ≤2; The raw materials are melted several times under the protective atmosphere, specifically: Nd, light rare earth elements RE, B, and low melting point elements T are placed at the bottom, Fe, Co, Cu, main group elements Q, and grain refining elements M are placed at the top, and the bottom raw materials are melted by an induction coil while the top raw materials are melted by a 60-120A current arc, and the melting is performed 4-6 times; After the alloy ingot is crushed, it is heated to a molten state under a protective atmosphere, and the resulting melt is overflowed onto a cooling roller to form an amorphous thin strip; The amorphous thin ribbon is subjected to a magnetic-thermal-mechanical multi-field coupling heat treatment to obtain a dual-phase composite magnetic material nanocrystalline ribbon; The nanocrystalline strips of the dual-phase composite magnetic material are powdered and sieved to obtain a precursor magnetic powder, the precursor magnetic powder is mixed with a coupling agent, a curing agent, a binder and a filler for pressing, and the pressed magnet is subjected to a heating reaction to obtain a bonded magnet; An alpha-Fe magnetic coating is uniformly coated on the surface of the bonded magnet to obtain a rare earth-poor dual-phase composite magnetic material.
2. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The amorphous thin strip has a thickness of 15-30 μm and a width of 5-10 mm, and the rotation speed of the cooling roller is 25-60 m / s.
3. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The magnetic-thermal-mechanical multi-field coupling heat treatment is specifically as follows: heating the temperature to 500-650°C at a heating rate of 2-5°C / min, applying an external magnetic field of 1-2T and a pressure of 100-300MPa simultaneously during the heating process, and keeping the temperature for 5-15min.
4. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The sieving is specifically sieving through a 120-mesh sieve, the pressing pressure is 1500-2000 MPa, and the pressing time is 30-60 s.
5. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The coupling agent is KH-550 silane, the curing agent is diaminodiphenyl sulfone, the adhesive is epoxy resin, and the filler is acetone; In the mixture of the precursor magnetic powder, coupling agent, curing agent, adhesive and filler, the coupling agent accounts for 1-2wt.%, the curing agent accounts for 20-25wt.%, the adhesive accounts for 3-5wt.%, and the filler accounts for 10-15wt.%.
6. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The heating reaction is specifically: keeping the temperature at 160-180° C. for 1-2 hours under the protection of argon atmosphere, and then cooling to room temperature.
7. The method for preparing a rare earth-poor dual-phase composite magnetic material according to claim 1, characterized in that: The thickness of the α-Fe magnetic coating does not exceed 0.5 mm; And / or, the α-Fe magnetic coating is composed of 30-35wt.% of α-Fe magnetic powder, 5-10wt.% of epoxy resin, 3-5wt.% of nano-silicon dioxide and 50-62wt.% of acetone; And / or, the particle size of the α-Fe magnetic powder is 10-125 μm.
Citation Information
Patent Citations
Pr / Nd based biphase composite permanent magnetic material and block body preparing method thereof
CN101425355A
High-abundance rare earth element-based nano double-phase composite material and preparation method thereof
CN115821173A